Facets of psychopathy in relation to trauma-exposure and posttraumatic stress symptomology in a sample of incarcerated male offenders. Issue 4 (19th December 2016) - Woodfield, Russell; Dhingra, Katie; Boduszek, Daniel; Debowska, Agata
Abstract : Purpose: The purpose of this paper is to investigate the moderating role of psychopathy facets on the relationship between traumatic exposure and posttraumatic stress disorder (PTSD) symptomology. Design/methodology/approach: Participants were male prisoners incarcerated in the UK. Findings: The analysis revealed differential associations between the two facets of psychopathy, with potentially traumatic events and symptoms of PTSD. Specifically, neither primary psychopathy nor trauma exposure were significantly related to PTSD, while secondary psychopathy was positively and significantly related with PTSD symptoms. Furthermore, the effect of trauma exposure on PTSD was found to depend on the level of secondary psychopathy. More specifically, trauma exposure was strongly and positively associated with PTSD symptoms for low levels of secondary psychopathy and negatively associated with PTSD symptomology for individuals with high levels of secondary psychopathy. Originality/value: The findings clarify linkages among psychopathy facets, trauma, and PTSD, and extend the understanding of the presentation of PTSD in male prisoners.